2017
DOI: 10.1088/1361-6528/aa5962
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale mapping of optical band gaps using monochromated electron energy loss spectroscopy

Abstract: Abstract.Using monochromated Electron Energy Loss Spectroscopy (EELS) in a probecorrected Scanning Transmission Electron Microscope (STEM) we demonstrate band gap mapping in ZnO/ZnCdO thin films with a spatial resolution below 10 nm and spectral precision of 20 meV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…All STEM imaging and EDX investigations were performed at an acceleration voltage of 300 kV with a probe convergence angle of 21 mrad and a resulting spatial resolution of approximately 0.08 nm. For band gap measurements in EELS an acceleration voltage of 60 kV was used to reduce relativistic effects that might otherwise mask the band gap signal [20]. The spectra were acquired using a Gatan GIF 965 spectrometer, with a collection angle of approximately 20 mrad.…”
Section: Methodsmentioning
confidence: 99%
“…All STEM imaging and EDX investigations were performed at an acceleration voltage of 300 kV with a probe convergence angle of 21 mrad and a resulting spatial resolution of approximately 0.08 nm. For band gap measurements in EELS an acceleration voltage of 60 kV was used to reduce relativistic effects that might otherwise mask the band gap signal [20]. The spectra were acquired using a Gatan GIF 965 spectrometer, with a collection angle of approximately 20 mrad.…”
Section: Methodsmentioning
confidence: 99%
“…However, we have previously 8 found that this model gives a high goodness of fit (R 2 > 0.97) for ZnO, and furthermore that the extracted band gap is close to that found by optical methods. 1 With c and E g as fitting parameters, the curve fit of Eq. (1) to the spectra in Fig.…”
Section: Iðeþmentioning
confidence: 99%
“…The band gap is a fundamental property of semiconductors, and control and manipulation of the optical band gap is of increasing interest both from a scientific view and for development of new applications. [1][2][3] This has led to the field of band gap engineering, where the optical band gap is manipulated through alloying or nanoscale modification of the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in aberration correction 15 and electron beam monochromation 16 over the past decade have facilitated the application of valence EELS toward a few semiconductor bandgap mapping efforts [17][18][19] although these studies have primarily targeted wide-gap materials (>3.0 eV). 18,20 While an energy resolution of 10 meV, or better, has been reported in a few cases, 21 and has allowed the opportunity to extract such information in narrower-gap materials (<3.0 eV), 17,22 FWHM values in the range 100-200 meV are more typical and accessible in most monochromated instruments.…”
Section: Introductionmentioning
confidence: 99%